CLINICAL SIGNIFICANCE OF VISFATIN AND HOMOCYSTEINE IN FORECASTING OF OSTEOARTHRITIS IN WOMEN OF PRE- AND POSTMENOPAUSAL AGE WITH TYPE 2 DIABETES MELLITUS - Zhuravlyova, L.V.; Cherpita V.О. (World of Medicine and Biology, 2022)
Type 2 diabetes mellitus is a leading cause of death and has high prevalence. Patients with type 2 diabetes mellitus are often diagnosed with osteoarthritis, the vast majority of cases are found in pre- and postmenopausal women due to decreased estrogen levels, as well as their numerous hormonal and metabolic disorders. The study determined the prognostic significance of visfatin and homocysteine in the development of osteoarthritis in pre- and postmenopausal women with type 2 diabetes mellitus and built a prognostic model for the development of osteoarthritis. We studied 82 pre- and postmenopausal women: 20 women (1 group) with isolated type 2 diabetes mellitus and 62 women (group 2) with comorbid type 2 diabetes mellitus and osteoarthritis. The study found that reliable predictors of osteoarthritis in women with type 2 diabetes mellitus in pre- and postmenopausal women were waist circumference, levels of very-low-density lipoproteins, visfatin and homocysteine, which were included in a prognostic model with high levels of sensitivity and specificity: 96.8 % and 90.0 %, respectively. The value of the area under the curve was 0.992±0.006 [95.0 % CI 0.979–1.000], p